2011
DOI: 10.1136/jcp.2011.089805
|View full text |Cite
|
Sign up to set email alerts
|

Ezrin expression predicts local recurrence and development of metastases in soft tissue sarcomas

Abstract: Ezrin independently predicts development of local recurrences and metastases in soft tissue sarcomas. The possibility of preoperative evaluation makes ezrin a potential marker for identification of high-risk sarcoma patients who would benefit from neoadjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Comparison of ezrin expression levels in tumour samples has revealed a clear association with tumour progression, metastatic spread and poor clinical outcome in several cancers, including breast cancer, malignant melanoma, ovarian carcinoma and soft tissue sarcomas [14][15][16][17]. In osteosarcoma, high ezrin expression is linked to pulmonary metastasis and a more aggressive course of disease [18].…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of ezrin expression levels in tumour samples has revealed a clear association with tumour progression, metastatic spread and poor clinical outcome in several cancers, including breast cancer, malignant melanoma, ovarian carcinoma and soft tissue sarcomas [14][15][16][17]. In osteosarcoma, high ezrin expression is linked to pulmonary metastasis and a more aggressive course of disease [18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, our study is retrospective and included only one TMA core per case. It is of note, however, that several recent studies used the same methods we have applied herein such as scoring system and TMA block 7,11,15,16. Nevetheless, the present findings remain to be confirmed by further studies.…”
Section: Discussionmentioning
confidence: 53%
“…Recently, many studies have suggested that increased ezrin expression was associated with poor outcome in various types of cancers, in various organs, including gastric carcinoma,7 colorectal carcinoma,8,9 nasopharyngeal carcinoma,10 esophageal SCC,11 breast carcinoma,12 osteosarcoma,13,14 various soft tissue sarcomas,15,16 cutaneous basal cell carcinoma and SCC,17 and melanoma 18. Some cohort studies19,21 suggested the distinct fuction of ezrin in tumor cell invasion or metastasis, however, no report to date has ever identified its favorable prognostic value.…”
Section: Discussionmentioning
confidence: 99%
“…The total number of patients included for meta-analysis was 4693, ranging from 40 to 487 per study. In total, 22 studies had data on OS [6], [7], [8], [10], [11], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], and 7 study have data on DFS [6], [9], [23], [33], [34], [35], [36]. 13 reports originated from Asia, 14 from Non Asia.…”
Section: Resultsmentioning
confidence: 99%